2017
DOI: 10.1002/fes3.101
|View full text |Cite
|
Sign up to set email alerts
|

Genetically engineered bananas resistant to Xanthomonas wilt disease and nematodes

Abstract: Banana is an important staple food crop feeding more than 100 million Africans, but is subject to severe productivity constraints due to a range of pests and diseases. Banana Xanthomonas wilt caused by Xanthomonas campestris pv. musacearum is capable of entirely destroying a plantation while nematodes can cause losses up to 50% and increase susceptibility to other pests and diseases. Development of improved varieties of banana is fundamental in order to tackle these challenges. However, the sterile nature of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 88 publications
0
29
0
Order By: Relevance
“…Economic losses in the range of $2-8 billion as a result of BXW have been reported over a decade within East Africa (Nkuba et al, 2015;Shimwela et al, in press;. As a result of the inconsistent adoption of recommended management options (Shimwela et al, 2016) and the lack of a resistant source in Musa germplasm (Tripathi et al, 2017), Xcm is likely to remain a continued threat within East and Central Africa.…”
Section: Managementmentioning
confidence: 99%
“…Economic losses in the range of $2-8 billion as a result of BXW have been reported over a decade within East Africa (Nkuba et al, 2015;Shimwela et al, in press;. As a result of the inconsistent adoption of recommended management options (Shimwela et al, 2016) and the lack of a resistant source in Musa germplasm (Tripathi et al, 2017), Xcm is likely to remain a continued threat within East and Central Africa.…”
Section: Managementmentioning
confidence: 99%
“…[112,113]. Furthermore, pyramiding of cystatins and chemodisruptive peptide into different crop plants has shown a high degree of nematode resistance and enhanced crop yields [114,115,116]. These approaches could be further combined with RNAi to give more effective and more durable transgenic resistance.…”
Section: Nematode Resistance Through Modern Approachesmentioning
confidence: 99%
“…Very recently, by screening the entire banana collection at the IITA, 13 banana varieties have been identified that are resistant to the bacterial banana wilt disease (Nakato et al, 2018). Until then, because no resistance source in banana germplasm had been detected, the only direct alternative solutions were to genetically modify banana with resistance genes identified in sweet pepper (Capsicum annuum) (Tripathi et al, 2017). From 2016 until today, cereal farmers across SSA experience heavy yield losses that threaten food security and trade, due to the devastation by a new alien invasive pest, the fall armyworm (Spodoptera frugiperda).…”
Section: Reducing the Yield Gapmentioning
confidence: 99%